Scoping Review: Potential of Bekul Fruit (Ziziphus jujube Mill.) as an Antidiabetic Agent in Patients with Type 2 Diabetes Mellitus - Windayani, Komang; Dirgahayu, Paramasari; Febrinasari, Ratih Puspita (Nusantara Science and Technology Proceedings, 2024)
Diabetes mellitus is a metabolic disorder characterized by high blood glucose (hyperglycemia) caused by damage or abnormalities in insulin production. Pharmacological therapy used as a treatment for diabetes mellitus in some patients has adverse side effects on the body, thus encouraging exploration to use natural ingredients as an alternative therapeutic source in reducing blood glucose. Therefore, a thorough review is needed to summarize scientific data and investigate the potential use of natural ingredients bekul fruit (Ziziphus jujube Mill.) in its role as an antidiabetic agent. This study used a scoping review with 4 databases: Pubmed, ScienceDirect, DOAJ and Google Scholar. The results of the scoping review of 5 scientific articles found that bekul fruit (Ziziphus jujube Mill.) is proven to have bioactive content that is rich in antioxidants such as phenolic/polyphenolic compounds (ferulic acid, caffeic acid, chlorogenic acid), flavonoids (quercetin, rutin, catechin), phytosterols, and inulin which have the potential as antidiabetic agents with different mechanisms of action in reducing blood glucose levels. Conclusion: bekul fruit (Ziziphus jujube Mill.) has the potential to be an alternative nutraceutical diet therapy in patients with diabetes mellitus.